Dangerous nation - Kagan, Robert (New York : Vintage Books, 2007)
"A reevaluation of America's place in the world from the colonial era to the turn of the twentieth century. Foreign-relations expert Kagan strips away the myth of America's isolationist tradition and reveals a more complicated reality: that Americans have been increasing their global power and influence steadily for the past four centuries. Even from the time of the Puritans, he reveals, America was no shining "city upon a hill" but an engine of commercial and territorial expansion that drove Native Americans, as well as French, Spanish, Russian, and ultimately even British power, from the North American continent. Even before the birth of the nation, Americans believed they were destined for global leadership. Underlying their ambitions, Kagan argues, was a set of ideas and ideals about the world and human nature."--Rsum de l'diteur
The first Imperialists -- The foreign policy of revolution -- Liberalism and expansion -- To the farewell address and beyond -- "Peaceful conquest" -- A republic in the age of monarchy -- The foreign policy of slavery -- Manifest destinies -- Beyond the national interest -- War and progress -- From power to ambition, from ambition to power -- Morality and hegemony
"America's foreign policy from Its earliest days to the dawn of the twentieth century"--Cover
Originally published: Knopf, c2006
Includes bibliographical references (p. [481]-506) and index
Keywords: United States -- Foreign relations -- To 1865; United States -- Foreign relations -- 1865-1921; United States -- Territorial expansion -- History; United States -- Foreign public opinion -- History